Narzędzia promocji w marketingu relacji - Sułkowski, Łukasz; Seliga, Robert (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The article presents partnership marketing as a tool for upgrading promotion activities of companies. The authors present the tools most recently used in the concept of partnership marketing and indicate their vital role in promotion activities. It can be claimed that establishing relations between a company and its customers or partners is what makes the promotion activities more effective. There are predictions of further development of both the idea and the applications of partnership marketing to finally result in their encompassing marketing activities in various economic sectors. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1183, s. 519-524